Investigating the effects of drug combinations and loss of the PRH/Hhex oncoprotein in CCA cells - Martin, Grace (2025)
Cholangiocarcinoma (CCA) is a group of malignancies that arises from the biliary epithelial cells that line the bile duct. Despite the emergence of new treatment modalities, patient prognosis is very poor and novel therapeutics are urgently needed. This project investigates Niclosamide, an anti-helminth drug, that was identified from a drug repurposing screen. In this thesis, I show that Niclosamide treatment over 72 hours can reduce CCA cell viability significantly more than normal Biliary Epithelial Cells (BECs). This reduction in cell viability is due in large part to Niclosamide-induced mitochondrial uncoupling that causes cellular stress and an imbalance in protein homeostasis. Niclosamide treatment is also shown to promote apoptosis after 24 hours of treatment and to have an anti-proliferative effect over 72 hours. The Proline Rich Homeodomain (PRH) protein, also known as the haematopoietically expressed homeobox (HHEX) protein, has recently been shown to act as an oncoprotein in CCA cells increasing cell proliferation and cell migration. Interestingly, Palbociclib was shown to abrogate cell proliferation in PRH-driven CCA cells through the inhibition of CDK4/6 activity. Here, Palbociclib is shown to selectively reduce the viability of CCA cell lines compared to BECs and to synergise with Niclosamide. At a phenotypic and protein level, the Niclosamide-Palbociclib combination is shown to effectively promote cell cycle arrest through multiple mechanisms. Thus, the combination of Niclosamide and Palbociclib is shown to provide a potent anti-CCA effect in 2D and 3D in vitro cancer models. PRH is substantially decreased by Niclosamide and Palbociclib dual therapy, which occurs through two independent mechanisms, whereby Niclosamide treatment induces PRH degradation by the proteasome, and PRH protein level also decreases upon Palbociclib-induced cell cycle arrest. Also, the drugs as single agents, and as a combination, are more effective in cells with high levels of PRH expression compared to cells with low levels of PRH expression. To understand the role of PRH in CCA further, the effects of PRH knockdown on CCA cells was studied through siRNA and shRNA protein knockdown and for the first time CRISPR-Cas mediated PRH knockout. These models shed light on the functions of the PRH protein in cell cycle and highlight previously undocumented roles of PRH in CCA cells in cell survival, cell metabolism and apoptosis. In conclusion, this thesis provides the first preclinical evaluation of Niclosamide-Palbociclib dual therapy for CCA and provides more information about the role of PRH in CCA biology that may lead to improved methods for the targeting of PRH in PRH-driven CCA.